Systematic Review: Pharmacists’ Level of Knowledge on Psychotropic Drug Administration - Yesi Lestari; Anna Wahyuni Widayanti; Satibi Satibi (Rumah Sakit Akademik Universitas Gadjah Mada, 2026)
Background: Pharmacists play a crucial role in patient care, often serving as primary sources of medication information. Psychotropic drugs require careful management due to their impact on the central nervous system and potential risks. However, pharmacists' knowledge of psychotropic drug administration varies, with gaps identified in understanding specific psychiatric disorders such as schizophrenia and ADHD. Training and continuous education are essential to enhance pharmacists' competency in psychotropic pharmacotherapy. This study aims to assess pharmacists' knowledge and attitudes toward psychotropic medications and to identify areas for improvement to optimise mental healthcare services.Method: A systematic review was conducted using the PRISMA method, using literature from Scopus, Google Scholar, ScienceDirect, and SpringerLink. The inclusion criteria focused on studies published between 2020 and 2024 that examined pharmacists' knowledge and practices in the administration of psychotropic drugs. Six relevant articles were analysed.Result: The findings indicate that pharmacists generally have positive attitudes toward patients with mental health conditions. However, their knowledge of psychotropic medications, especially in terms of proper administration, side effects, and treatment adherence, remains insufficient. Key barriers include a lack of formal training, limited continuing education, and weak regulatory frameworks.Conclusion: To improve pharmacists' role in psychotropic medication management, structured training programs, stricter regulations, and continuous professional education are needed. These measures will enhance pharmacists' competency and improve patient outcomes in mental healthcare.